Epidemiology of Tetracycline Resistance Determinants in Shigella spp. and Enteroinvasive Escherichia coli: Characterization and Dissemination of tet(A)-1 - Hartman, Antoinette B. (American Society for Microbiology, 2003)
To make a comprehensive study of tetracycline resistance determinant distribution in the genus Shigella, a collection of 577 clinical isolates of Shigella spp. and enteroinvasive Escherichia coli (EIEC) from a variety of geographical locations was screened to identify tetracycline-resistant strains. The 459 tetracycline-resistant isolates identified were then screened by PCR analysis to determine the distribution in these strains of tetracycline efflux resistance determinants belonging to classes A to E, G, and H that have been identified in gram-negative bacteria. Only classes A to D were represented in these strains. Although Tet B was the predominant determinant in all geographical locations, there were geographical and species differences in the distribution of resistance determinants. An allele of tet(A), designated tet(A)-1, was identified and sequenced, and the 8.6-kb plasmid containing determinant Tet A-1, designated pSSTA-1, was found to have homologies to portions of a Salmonella enterica cryptic plasmid and the broad-host-range resistance plasmid RSF1010. This allele and pSSTA-1 were used as epidemiological markers to monitor clonal and horizontal transmission of determinant Tet A-1. An analysis of serotype, distribution of tetracycline resistance determinants, and resistance profiles indicated that both clonal spread and horizontal transfer had contributed to the spread of specific tetracycline resistance determinants in these populations and demonstrated the use of these parameters as an epidemiological tool to follow the transmission of determinants and strains.